Population Density of Migrating Barn Swallow (Hirundo rustica) in Serian Town Sarawak. - Mohamad Amyirrul, Mohd Aris Fadillah (Universiti Malaysia Sarawak, (UNIMAS), 2015)
The population of Barn Swallow has been declining over the years in each state. Barn Swallows are known by many ornithologists as distant travelers that cross thousands of miles during winter from the north region to south region. This research was conducted at Serian District, Town that is very famous for the perching sites of Barn Swallow. The main objective of this research is to estimate the population density of Barn Swallow in Serian town. The density of Barn Swallow in Serian Town is five individual in one kilometer square. The Barn Swallow was sighted perching at three area that were wired cable along the road, building in Serian Town and tree. To calculate the number of barns swallow, estimation method was used.